How can Problem Posing Pedagogy help to enhance ninth grade EFL students’ interests and language needs? (2020)
ABSTRACT: This action research aimed to explore how Problem Posing Pedagogy can enhance ninth graders’ interests and language needs. The participants were 37 students at a private school in Bello, Colombia. The pedagogical actions followed six stages: Describe the code, Define the problem, Personalize the problem, Analyze the root causes of the problem, Strategize possible responses, and Application. Data collection instruments included student surveys, student journals, and the teacher journal. Findings suggest that implementing Problem Posing helped promote students’ interest and engagement in the English class, and boost their interaction during classroom activities. Nevertheless, the application of this pedagogy may also face some resistance on the part of students, preventing them from enjoying the project, and experiencing a more significant learning.